Synthesis of new 3-(substituted-phenyl)-N-(2-hydroxy-2-(substituted-phenyl)ethyl)-N-methylthiophene-2-sulfonamide derivatives as antiproliferative agents - Pawar, Chandrakant; Pansare, Dattatraya; Shinde, Devanand (European Journal of Chemistry, 2018)
In the present work, we report the synthesis of a series of 3-(substituted phenyl)-N-(2-hydroxy-2-(substituted-phenyl)ethyl)-N-methylthiophene-2-sulfonamide derivatives through Suzuki and Buchwald reaction. We have optimized methodology for targets from milligram to multi-gram scale. The newly synthesized compounds were characterized by 1H NMR, 19F NMR, 13C NMR, LC-MS techniques and purity was further checked by HPLC. The compounds were evaluated for their in-vitro antiproliferative activity against MCF-7, HeLa, A-549 and Du-145 cancer cell lines by CCK-8 assay. The preliminary bioassay suggests that most of the compounds show antiproliferation with different degrees and 5-fluorouracil was used as positive control. Among these compounds 2d, 2g, 2i, 4e, 4h and 4k are most active compared to the standard. All the synthesized compounds show IC50 values from 1.82-9.52 µM in different cell lines. Amongst these, compounds 2d, 2g, 2i, 4e, 4h and 4k were most potent, with IC50 values ranging from 1.82-4.28 µM in different cell lines.